2016
DOI: 10.3748/wjg.v22.i35.7938
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic aspects of c-MYC signaling in inflammatory and cancerous colonic diseases

Abstract: Colonic inflammation is required to heal infections, wounds, and maintain tissue homeostasis. As the seventh hallmark of cancer, however, it may affect all phases of tumor development, including tumor initiation, promotion, invasion and metastatic dissemination, and also evasion immune surveillance. Inflammation acts as a cellular stressor and may trigger DNA damage or genetic instability, and, further, chronic inflammation can provoke genetic mutations and epigenetic mechanisms that promote malignant cell tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 124 publications
1
52
2
Order By: Relevance
“…A lower miR-98 expression in glioma cell lines and related tissues was observed and its upregulation can promote glioma cell apoptosis and inhibit the Bcl-2 expression. 32 PCNA is a kind of much conserved protein in archaebacteria as well as several eukaryotic species, of which the decrease marks many proliferative diseases for PCNA which is a general proliferative marker with no discrepancies of gender or age. 28 Hu et al 8 have reported that miR-98 can decrease Bcl-2 and upregulate Bax by targeting MAPK6 in human vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…A lower miR-98 expression in glioma cell lines and related tissues was observed and its upregulation can promote glioma cell apoptosis and inhibit the Bcl-2 expression. 32 PCNA is a kind of much conserved protein in archaebacteria as well as several eukaryotic species, of which the decrease marks many proliferative diseases for PCNA which is a general proliferative marker with no discrepancies of gender or age. 28 Hu et al 8 have reported that miR-98 can decrease Bcl-2 and upregulate Bax by targeting MAPK6 in human vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 ] Proto‐oncogene c‐Myc is a central regulator of cellular proliferation, and plays a key role in cell cycle progression, apoptosis, and cellular transformation. [ 38,39 ] The downregulation of c‐Myc is necessary for cell cycle arrest. [ 38 ] Thus, we examined the effect of butyrate on c‐Myc expression and found that butyrate greatly reduced c‐Myc protein levels in both DCA‐RCL and HCT‐116 cells (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…[ 38,39 ] The downregulation of c‐Myc is necessary for cell cycle arrest. [ 38 ] Thus, we examined the effect of butyrate on c‐Myc expression and found that butyrate greatly reduced c‐Myc protein levels in both DCA‐RCL and HCT‐116 cells (Figure 6). This finding is consistent with that cell cycle progression from the G0/G1 into the S phase is tightly controlled by c‐Myc by regulating the expression of cyclins, cyclin dependent kinases.…”
Section: Discussionmentioning
confidence: 99%
“…MYC is well known for the role in the progression of CRC [43]. MYC is frequently deregulated in inflammation and the expression is affected by DNA-methylation [11]. PPARGC1A encodes a transcriptional coactivator that regulates the genes involved in energy metabolism [29].…”
Section: Rab21 and Ninj1 Are Related To Cell Adhesion And Migration mentioning
confidence: 99%
“…Inflammatory biomarkers such as NLR, LMR and PLR have been suggested as prognostic markers in colorectal cancer [7][8][9][10]. Chronic inflammation can trigger genetic mutations and epigenetic alternations that promote malignant cell transformation [11]. However, the inflammatory interactions with colon involve various modes of action such as immune cells, cytokines, and other immune mediators in virtually all sequence of CRC progression, including initiation, progression, and metastasis [12].…”
Section: Introductionmentioning
confidence: 99%